Sexual behaviours and lifestyles associated with poor mental health among British adults during the early phase of the COVID-19 pandemic: findings from a large, quasirepresentative, cross-sectional web-panel survey (Natsal-COVID) - Soazig Clifton; Pam Sonnenberg; Nigel Field; Catherine H Mercer; Andrew Copas; Julie Riddell; Raquel Bosó Pérez; Emily Dema; Emily Jordan; Kirstin Rebecca Mitchell (BMJ Public Health)
Objective A national lockdown was implemented in the UK from March 2020 to reduce COVID-19 transmission which impacted mental health and sexual behaviours. This study investigated the association between sexual behaviours and poor mental health among British adults during the early phase of the COVID-19 pandemic.Methods and analysis The Natsal-COVID web-panel survey is a quasirepresentative population sample of 6654 British adults (18–59 years; July–August 2020). We examined associations between sexual behaviours in the 4 months after the start of the first lockdown and poor mental health in the past 2 weeks (Patient Health Questionnaire (PHQ)-2 for depression and Generalised Anxiety Disorder-2 for anxiety, combined into PHQ-4 for psychological distress) using multivariable logistic regression.Results Among participants with complete data (n=6500), 54.8% reported psychological distress (28.0% mild, 15.6% moderate and 11.3% severe). After adjusting for age, gender and relationship status, psychological distress was higher among participants identifying as bisexual (adjusted OR 2.13 (95% CI: 1.61 to 2.82)) or other minority sexual identities (3.20, 1.60–6.41) compared with heterosexual. Psychological distress was also higher among those reporting experiencing sexual difficulties (very often/always vs never: 3.70, 2.64–5.18) or 2+partners since lockdown (compared with one: 3.90, 2.78–5.47). Psychological distress was less among participants reporting higher sexual frequency (5+occasions of sex in the past 4 weeks vs none: 0.64, 0.48–0.86).Conclusions Psychological distress was common among British adults during the COVID-19 pandemic, and this was associated with sexual behaviours. These findings have important implications for the design and implementation of interventions for populations at risk of poor mental and sexual health, including during international crises.